The Change in External Genital and Estrogen Level of Bali Cattle During Estrus - Laksmi, Desak Nyoman Dewi Indira; Trilaksana, I Gusti Ngurah Bagus (Journal of Veterinary and Animal Sciences; Vol 3 No 1 (2020), 2020)
The successful application of reproductive technology requires knowledge of estrus cycle and the ability to detect estrus of Bali cattle. Estrus in cattle lasts for 8-30 hours showed by the acceptance of males for copulation. In this phase, estrogen levels reach maximum levels. High levels of estrogen cause signs of estrus, and changes in the reproductive organs. This study aims to determine estrogen levels during estrus and external genital changes during estrus. This research was an observational analytic study with cross-sectional study design. The samples used in this study were Bali cattle during estrus. The samples had healthy status without any signs of disease. Blood samples were taken through the jugular vein were then centrifuged to obtain serum. The obtained serum was examined for estrogen hormone levels. Mechanical measurements of hormone levels checked by using the Direct Elisa, Double Antibody Sandwich. Blood samples were collected from several SIMANTRI in Mengwi District, Badung Regency. The results showed in Bali cattle external genitals change when estrus, namely redness of the vaginal mucosa, discharge from the vagina and swelling of the vulva. While estrogen levels when estrus is 69.80 pg/ ml. Further research needs to be continued to measure the quality of ovulation after estrus.